2017
DOI: 10.1002/2016tc004405
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Signature of the Continental Crust: What Thermodynamics Says. An Example From the Italian Peninsula

Abstract: Unraveling the temperature distribution and composition of Earth's crust is key for understanding its origin, evolution, and mechanical behavior. Models of compressional (VP) and shear wave (VS) velocity are obtained from seismological studies and can be interpreted in terms of temperature and composition, using relationship defined through laboratory experiments. These empirical evidences often do not properly account for the effects driven by temperature, pressure, water content, and phase change of minerals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 75 publications
(106 reference statements)
0
21
0
Order By: Relevance
“…The − quartz transition is dominantly temperature dependent and relies on the assumption of sufficient modal quartz in the bulk rock. In Diaferia and Cammarano (2017) we demonstrated that a quartz content below <20% vol is already sufficient to produce an appreciable increase in V P ∕V S at the transition, suggesting that especially within the upper and middle crust the detection of the quartz transition might be seismically relevant. However, caution is necessary for geologically complex areas with expected structural and lithological heterogeneity that can undermine the reliability of RFs (from which V P ∕V S are derived) due to the presence of dipping interfaces and anisotropy.…”
Section: Temperature At Depthmentioning
confidence: 73%
See 2 more Smart Citations
“…The − quartz transition is dominantly temperature dependent and relies on the assumption of sufficient modal quartz in the bulk rock. In Diaferia and Cammarano (2017) we demonstrated that a quartz content below <20% vol is already sufficient to produce an appreciable increase in V P ∕V S at the transition, suggesting that especially within the upper and middle crust the detection of the quartz transition might be seismically relevant. However, caution is necessary for geologically complex areas with expected structural and lithological heterogeneity that can undermine the reliability of RFs (from which V P ∕V S are derived) due to the presence of dipping interfaces and anisotropy.…”
Section: Temperature At Depthmentioning
confidence: 73%
“…Following Piana Agostinetti & Malinverno (2010Malinverno ( , 2018 and Gao and Lekic (2018), we decide to treat V P ∕V S as a variable that can be randomly perturbed along the chain. As a matter of fact, both laboratory experiments (Peng & Redfern, 2013;Ohno et al, 2006) and thermodynamic modeling (Diaferia & Cammarano, 2017) suggest that V P ∕V S can strongly vary at crustal depths as a result of the phase transition of quartz from its to form. Therefore, given the scope of this study, we find that fixing V P ∕V S at an arbitrary value will hamper an unbiased interpretation.…”
Section: The Joint Inversion Strategy 231 the Rj-mcmc Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we analysed only the sonic log data, although we are conscious that the variability of seismic wave velocity and density is a function also of temperature, pressure, chemical composition and water content 53,54 . Of all these factors, temperature may be the dominant influence on Vp and Vs, especially in areas of significant magmatism.…”
Section: Discussionmentioning
confidence: 99%
“…Within the crust, P wave velocities are calculated using empirical V P ‐density relationships from Brocher (2005), whereas S wave velocities are calculated assuming a constant V P / V S = 1.73 ratio (Figure 10b). Indeed, an option including crustal material files is kept for future or if user have a thermodynamic database for the crustal chemical composition (e.g., Diaferia & Cammarano, 2017). Below 400 km depth (base of the model), velocities from ak135 model are used.…”
Section: Post‐processing Toolboxmentioning
confidence: 99%